Analisis Efisiensi Penggunaan Tempat Tidur Di RSJD Dr. Arif Zainudin Surakarta - Septiyowati, Shela Anik; Igiany, Prita Devy; Pertiwi, Julia (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda (JIPIKI), 2024)
Health Statistics provide information about people’s health and use of health services. The percentage of bed use in health service facilities been formulated consists of 4 parameters, namely BOR, LOS, TOI, BTO which can be depicted in a graphic known as Barber Johnson. The purpose of this study is to analyze the efficiency of bed use based on Barber Johnson at RSJD Dr. Arif Zainudin Surakarta in 2021. The type of research used is quantitative descriptive with Cross sectional design. Population in the form of monthly SHRI recapitulation. The results of this study show that the BOR calculation in 2021 was 48.43% in (Quarter 1), 58.82% (Quarter II), 46.56% (Quarter III), 42.63% (Quarter IV). 20-day AVLOS (Quarter I), 20 days (Quarter II), 18 days (Quarter III), 19 days (Quarter IV), TOI 21 days (Quarter I), 14 days (Quarter II), 21 days (Quarter III), 26 days (Quarter IV), BTO 2 times (Quarter I), 3 times (Quarter II), 2 times (Quarter III and IV). From the analysis conducted, the use of beds in RSJD has not been efficient. To improve the efficiency of bed use, hospital management further improves quality of service and limits value of inpatient indicators according to mental hospitals.